The other Einstein [large type] : a novel - Benedict, Marie (Thorndike Press, a part of Gale, Cengage Learning, 2016)
"The Other Einstein offers us a window into a brilliant, fascinating woman whose light was lost in Einstein's enormous shadow. It is the story of Einstein's wife, a brilliant physicist in her own right, whose contribution to the special theory of relativity is hotly debated and may have been inspired by her own profound and very personal insight. Mitza Maric has always been a little different from other girls. Most twenty-year-olds are wives by now, not studying physics at an elite Zurich university with only male students trying to outdo her clever calculations. But Mitza is smart enough to know that, for her, math is an easier path than marriage. And then fellow student Albert Einstein takes an interest in her, and the world turns sideways. Theirs becomes a partnership of the mind and of the heart, but there might not be room for more than one genius in a marriage."--Amazon.com